Lipid Peroxidation and Antioxidant Activity in Molting Stages of Mud Crab (Scylla serrata) - Salaenoi, Jintana; Setthamongkol, Pakawan; Srimeetian, Pattarawadee; Satapornvanit, Kriengkrai (Agriculture and Natural Resources, 2015)
Lipid peroxidation (LPO) is the process whereby oxygen free radicals steal electrons from polyunsaturated fatty acids of cell membranes, initiating a self-propagating chain reaction and the endproducts of the reactions are dangerous to the viability of cells. It is used as an indicator of oxidative stress or the amount of free radicals in cells and tissues. The observation of LPO activities in various organs of mud crab (Scylla serrata) over the molting cycle showed evidence that supported the functions of free radicals. LPO in the intermolt stage was significantly (P < 0.05) lower than at the premolt stage. The LPO activities gradually increased when the crab entered the premolt stage which was detected in the haemolymph, gill, hepatopancreas, integument and muscle of crabs. The hepatopancreas seemed to be the organ where the free radical processes occurred. LPO in the haemolymph, integument and gills had the highest levels 2 d before molting while the activities in the hepatopancreas showed distinguishing functions 2 wk before molting. The determination of antioxidant activity using free radical scavengers showed the same pattern in the gills, meat, hepatopancreas and claws. The activities gradually decreased from the intermolt stage until they reached a minimum in the early postmolt, and then increased again at late postmolt. It clearly indicated that LPO activities in the molting cycle corresponded with the physiology during the stage changing and adaptation of crab.